Pengaruh Fasilitas Sekolah Terhadap Kemampuan Dan Motivasi Belajar Siswa Smp Al Ulum Terpadu Medan - Harahap, Adelia; Sabrina Sabrina; Saripa aini simbolon; Suci dahlya narpila (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This research aims to analyze the influence of school facilities on students' learning abilities and motivation at Al Ulum Integrated Middle School, Medan. With a descriptive qualitative approach, data was collected through observation, in-depth interviews, and document review. Facilities available at the school include air-conditioned classrooms, computer laboratories, libraries, mosques and sports fields. The research results show that school facilities have a very important role in supporting the learning process.Adequate facilities, such as classrooms equipped with projectors and air conditioning, can improve students' concentration and understanding of the lesson material. These findings confirm that adequate facilities not only support academic aspects, but also play an important role in building students' intrinsic motivation. Therefore, improving the quality and accessibility of educational facilities is very important to create a conducive learning environment. It is hoped that this research can provide valuable input for schools and stakeholders in efforts to improve the quality of education.Keywords: school; facilities ;learning; motivation